Some soluble groups of finite rank and some related matrix groups - Wehrfritz, B.A.F. (Український математичний журнал, 1991)
Let G be a torsion-free soluble group of finite rank and F ane field. The group algebra FG is an Ore domain; let D denote its division ring of quotients. it Seems likely that D is always locally residually finite-dimensional over F. this is certainly so in the non-modular case. Here in some special situations we settle the modular case. We include some applications to groups of matrices. Нехай G — розв'язна група без кручення скінченного рангу і F — поле. Групова алгебра FG являється областю Оре; і нехай D — її тіло часток. Ймовірно, що D завжди локально резидуально скінченно-вимірне над F. Це безперечно так в немодулярному випадку. В деяких спеціальних ситуаціях ми розглядаємо модулярний випадок. Ми включаємо деякі застосування до груп матриць.